Automatic Water Level Control With Dry Run Protection of Pump - Sen, Satyaki; Paul, Mayukh; Bandyopadhyay, Monosiz; De, Riddhi (International Journal of Computer Sciences and Engineering, 2025)
Water Level Measurement & Control forms an important part of any process in the industries as well as domestic purposes. It is generally observed that the measurement and control of liquid level is done either with the help of various continuous control strategies employing Proportional-Integral(PI)/Proportional-Integral-Derivative(PID) Controller in many plants where as in many other applications discrete control of pump starting and stopping is done for both for industrial & domestic purposes. Here in this particular work we propose a automatic liquid level monitoring & modified control strategy in the control algorithm which helps the pump not to operate when there is no water in the underground tank thus preventing the dry run of the pump helping in conservation of energy, preventing water wastage as well as protecting the pump from operating under dry run condition by switching the pump off. The system designed uses Arduino UNO as the Microcontroller board actuating the control action via a relay circuit to turn on or off a operating Dc pump as a prototype model.